Python Programming Workshops as OBI Preparation - Zanatta, Enzo; da Silva, Mariana Krein; Brusso, Marcos José (Seven Editora, 2023)
The Brazilian Programming Olympiad, (OBI) is a competition organized by the Institute of Computing at UNICAMP. The OBI is organized into two modalities, each divided into levels, the modalities are Initiation and Programming. The initiation modality requires students to answer logic and computational reasoning questions. The Programming modality requires students to solve programming questions, students must choose one of the languages that are allowed in the test to solve the questions. The best students in both categories are invited to the OBI Olympic week at the UNICAMP Institute of Computing, where they participate in courses and training from basic to advanced. The purpose of carrying out the programming workshops was to prepare students interested in programming and computing to participate in the OBI in the programming modality with the Python language. DOI: https://doi.org/10.56238/methofocusinterv1-063